Comparison of the Inhibitory Effects of Delphinidin and Its Glycosides on Cell Transformation - Sogo, Takayuki; Kumamoto, Takuma; Ishida, Hisako; Hisanaga, Ayami; Sakao, Kozue; Terahara, Norihiko; Wada, Koji; Hou, De-Xing (Planta Medica, 2015)
Although anthocyanins are major forms distributed in many plant foods and promising as chemopreventive source, many molecular data are obtained from anthocyanidins, showing their low bioavailability. This study aims to clarify the inhibitory effects of delphinidin glycosides on cell transformation comparing them to those of delphinidin. Screening data revealed that delphinidin 3-sambubioside could directly bind to MAPK/ERK kinase 1. Affinity assay data confirmed that delphinidin 3-sambubioside had higher binding affinity to MAPK/ERK kinase 1 than ERK1/2 and B-Raf. Colony assay data further demonstrated that delphinidin 3-sambubioside inhibited 12-O- tetradecanoylphorbol-13-acetate-induced phosphorylation of MAPK/ERK kinase 1 and sequentially suppressed cell transformation. All of these effects caused by delphinidin 3-sambubioside were weaker than those by its aglycon, delphinidin. Our data suggested that the weaker anti- transformation activity of delphinidin glycosides compared to that of their aglycon is due to lower binding affinity to the target molecule MAPK/ERK kinase 1.
Keywords: delphinidin 3-sambubioside; delphinidin; MEK1; cell transformation